Patient Experience Regarding Medication-Related Information Received in a Rural Private Polyclinic Setting in Vietnam - Quang Loc Duyen Vo MSc, BPharm; Minh Trung Nguyen BMed; Thi Ngoc Yen Dang MSc, BPharm; Thi Hong Dung Quach MSc, BPharm; Huynh Kim Ngoc Truong MSc, BPharm; Rebecca Susan Dewey MPhys, PhD; Thi Thu Tran BPharm; Van De Tran PhD (Journal of Patient Experience)
Inadequate provision of medication-related information can lead to nonadherence to treatment. This study aims to investigate patient satisfaction regarding medication-related information provided by healthcare professionals and to identify factors associated with patient experience regarding information. A cross-sectional descriptive study was conducted in October 2023 among 400 patients at a rural private polyclinic in Ben Tre, Vietnam by using a self-administered questionnaire. The key findings of this study showed that over half of the participants expressed overall satisfaction with the information provided (52%), with 57.5% satisfaction on the action and use subscale, and 56.8% satisfaction on the potential problems subscale. Patients aged 41 to 60 ( P  = .018), those older than 60 ( P  = .001), those with more than 2 dependents ( P  = .038), and those receiving information only from nurses ( P  = .009) were more likely to be satisfied with the information they received. Patient satisfaction with medication-related information received was low. Healthcare professionals should ensure timely and comprehensive communication about medications, particularly regarding potential side effects. While this study primarily focused on satisfaction, the closely related concept of patient experience warrants further exploration in future studies with a more deliberate focus.